Загальне поняття та визначення функцій судів загальної юрисдикції. - Нестерчук, Лілія Петрівна; Нестерчук, Лилия Петровна; Nesterchuk, L (My University, 2011)
An attempt to ﬁ nd out what behaves to the notion of general jurisdiction courts functions, applying the methods of classiﬁ cation of general and spe- cial signs of functions of these general jurisdiction courts is undertaken in the article. It is indicated on the necessity of ﬁ nding out of essence and main- tenance of functions of general jurisdiction courts for Ukraine, differentiation of concepts, which touches forms, methods and directions of court activity. The effective functioning of general jurisdiction courts in Ukraine hinders to violation of rights and freedoms of man and citizen, shuts out the appropria- tion of judicial department by any other public authority.
Нестерчук. Л.П. Загальне поняття та визначення функцій судів загальної юрисдикції./ Л.П.Нестерчук // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 43. С.226 - 233.
Keywords: Конституційне право; Функції судів загальной юрисдикції; Розмежування функцій судів; Разограничение функций судов; Функции судов общей юрисдикции; Конституционное право; constitutional law; The functions of courts of general jurisdiction; Razogranichenie functions of the courts